Optimization of curdlan production and ultrasound assisted extraction processes from Priestia megaterium - Natasha Aquinas; Bhat M. Ramananda; Subbalaxmi Selvaraj (Scientific Reports)
Abstract In this study, the upstream and downstream production processes of curdlan from Priestia megaterium were optimized to enhance its yield. Additionally, a novel extraction method was developed for curdlan recovery. Optimization studies were conducted using Central composite design (CCD). Curdlan yield improved from 0.15 g/L (unoptimized) to 0.46 g/L (3-fold increase) when fermentation was carried out in CCD-optimized media of (w/v) sucrose 20%, urea 0.1%, KH2PO4 0.02%, agitation speed 250 rpm. To further enhance curdlan yield during extraction, ultrasonication was incorporated as a novel step into the conventional method of acid/alkali-assisted curdlan recovery. A two-step optimization was chosen for extraction, namely, one-factor-at-a-time (OFAT) and CCD, wherein the optimized extraction parameters were determined to be 25 s sonication, 1 N NaOH, and 2 h solubilization time. The curdlan yield improved by 1.5-fold (0.70 g/L) post optimization, in comparison with unoptimized conventional extraction step. Finally, the biopolymer was validated through characterization by nuclear magnetic resonance (NMR) which showed characteristic curdlan spectra in the13C and1H NMR studies. To the best of our knowledge, this study represents the first documented report on curdlan extraction using this novel method of ultrasonication.